HOW CAN THEY SURVIVE ON EDUCATION PROCESS - Muhaini, Muhaini; Surya, Dedy; Alfatah, Muhammad Qori (Proceeding International Seminar of Islamic Studies, 2023)
Continuing education at a boarding school is quite challenging for students. Not only are they faced with the complexity of other problems, which are not found in conventional schools. This study explores the factors that cause students attending Dayah Nurul Ulum, Peureulak, East Aceh, Aceh, Indonesia, to persist with the learning process in the boarding school system. Using a qualitative case study research approach, empirical data was collected through in-depth interviews with students who have attended the school for 6 years. Through Stolz’s adversity quotient framework, this study found that santris’ resilience in completing their education in dayah is supported by several factors, namely: (1) optimistic attitude, (2) adaptability, (3) emotion management skills, and (4) social support. This article also argues that their internal motivation and high self-esteem as santri are also reinforcing factors for their success to survive.